Necrotizing sialometaplasia of the oral palate: a rare cause of painful mouth ulceration. - BELHAJ, NAJOUA; H.RAHIM; I.BOUMENDIL; H.AIT TALEB OUMHANED; S.NITASSI; A.OUJILAL; R.BENCHEIKH; M.A.BENBOUZID; L.ESSAKALLI (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Necrotizing sialometaplasia (NMS) is a rare benign inflammatory condition affecting the salivary glands. This pathology mainly affects the accessory salivary glands of the palate. We present a patient who consults for painful bleeding ulcers